Continuing professional development in mental health: Promoting dialogue and reflection through art. (September 2018) - De Vecchi, Nadia; Kenny, Amanda; Dickson-Swift, Virginia; Kidd, Susan
Abstract: International policy mandates that mental health consumers and carers are involved in the continuing professional development of nurses. However, within the literature, continuing professional development of mental health nurses continues to be delivered in didactic formats, with few examples of mental health nurses and consumers engaging together in the process. Consumers and carers are often excluded from professional development programs because of structural discrimination. Where they are included, it is often through storytelling that has been sanitised of challenging practice issues. There are few opportunities for reflection on practice. The purpose of this discussion article is to create debate about the involvement of mental health consumers and carers in professional development. Educators should consider artmaking between mental health consumers, carers and clinicians as a useful participatory process to support professional development, co-learning, mutual dialogue and reflection on practice. Highlights: Mental health policy mandates consumer involvement in professional development. Consumers are excluded from professional development because of discrimination. Reflection is vital for practice change but neglected in professional development. Artmaking can engage consumers and nurses in mutual reflection and dialogue. Participatory artmaking can enable consumer knowledge to be included in practice.